Mind wandering “Ahas” versus mindful reasoning: alternative routes to creative solutions - Zedelius, Claire M.; Schooler, Jonathan W. (Frontiers in Psychology, 2015)
Based on mixed results linking both mindfulness and its opposing construct mind wandering to enhanced creativity, we predicted that the relationship between mindfulness and creativity might depend on whether creative problems are approached through analytic strategy or through “insight” (i.e., sudden awareness of a solution). Study 1 investigated the relationship between trait mindfulness and compound remote associates problem solving as a function of participants’ self-reported approach to each problem. The results revealed a negative relationship between mindfulness and problem-solving overall. However, more detailed analysis revealed that mindfulness was associated with impaired problem solving when approaching problems with insight, but increased problem solving when using analysis. In Study 2, we manipulated participants’ problem-solving approach through instructions. We again found a negative relationship between mindfulness and creative performance in general, however, more mindful participants again performed better when instructed to approach problems analytically.